PENGARUH CURAHAN WAKTU KERJA WANITA TANI TEMBAKAU TERHADAP PENERIMAAN KELUARGA DI KECAMATAN JUMO KABUPATEN TEMANGGUNG - Rizki Iqbal Maulana; Siwi Gayatri; Tutik Dalmiyatun (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2019)
The purpose of this study was to analyze 1) How the time spent by female farm laborers in tobacco commodities in Jumo District, Temanggung Regency 2) What is the contribution of women's acceptance to family acceptance 3) What is the effect of the outpouring of women's working time on tobacco plantations on family acceptance. This research was conducted in February - March 2018 in Jumo District, Temanggung Regency. The research method was survey. The method of determining the sample was done by Slovin method with a total of 82 samples. The analysis was descriptive analysis and simple regression analysis. The activities of women tobacco farmers are divided from planting land preparation, tobacco seed preparation, tobacco seed nursery, planting, maintenance, harvesting, and post-harvest. The results showed that the average HKSP of female farmers was 764 hours/activity, the average income of women tobacco farmers in Jumo District was Rp.5,596,451. Family welfare can be seen from the dual role of women farmers as housewives and as tobacco farming women to increase family acceptance. There is no significant effect between the working time of female farmers on the acceptance of women tobacco farmers in Jumo District Temanggung Regency because the acceptance of female farmers is given based on activities. There are reasons that keep women farmers working for example their role in to fill busy life and become a side job in addition to their role in domestic sector as housewife.